1990
DOI: 10.1038/jcbfm.1990.99
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Hemodynamic Activation of Postischemic Rat Brain by Cortical Spreading Depression

Abstract: Summary: Following transient ischemia of the brain, the coupling between somatosensory activation and the he modynamic-metabolic response is abolished for a certain period despite the partial recovery of somatosensory evoked responses. To determine whether this disturbance is due to alterations of the stimulus-induced neuronal ex citation or to a breakdown of the coupling mechanisms, cortical spreading depression was used as a metabolic stimulus in rats before and after ischemia. Adult rats were subjected to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…In fact, spreading depression is an energy-requiring process that leads to substantial activation of energy-producing me tabolism. Measurements of cerebral metabolic rate of glucose carried out under similar conditions of repetitive spreading depression as in the present study revealed an increase by 77% (Kocher, 1990). Other authors reported a threefold increase in glu cose consumption (Gjedde et al, 1981) and a 45% rise of oxygen consumption (Mayevsky and Weiss, 1991).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In fact, spreading depression is an energy-requiring process that leads to substantial activation of energy-producing me tabolism. Measurements of cerebral metabolic rate of glucose carried out under similar conditions of repetitive spreading depression as in the present study revealed an increase by 77% (Kocher, 1990). Other authors reported a threefold increase in glu cose consumption (Gjedde et al, 1981) and a 45% rise of oxygen consumption (Mayevsky and Weiss, 1991).…”
Section: Discussionsupporting
confidence: 78%
“…Spreading depression substantially increases the metabolic rate to cope with the in creased workload of ion exchange pumps (Gjedde et aI., 1981). In the intact brain, this rise in meta bolic activity is coupled to the parallel increase of blood flow to ensure adequate oxygen delivery (Hansen et aI., 1980;Kocher, 1990). It is possible that this coupling is disturbed in the surroundings of the infarct and that this region suffers a period of relative hypoxia during the passage of each depo larization.…”
mentioning
confidence: 99%
“…It is therefore possible that the tissue be comes transiently hypoxic during these episodes. This could explain why, in the present study, the duration of periinfarct DC deflections was as long as 10 min, i.e., much longer than the DC deflection during spreading depression in normal cortex, which lasts only �2 min (Mies and Paschen, 1984;Kocher, 1990). This observation is in line with an earlier study by Nedergaard and Astrup (1 986), who reported that DC deflections in the periinfarct area last for up to 8 min.…”
Section: ��--------------------[mentioning
confidence: 48%
“…However, it is con ceivable that the combination of a marginal isch emia with repeated cell depolarizations creates a pathophysiological situation that may result in irre versible cell damage. In fact, in the intact animal, spreading depression is associated with an in creased metabolic rate for glucose (Shinohara et al , 1979), which is coupled to a similar rise in blood flow (Kocher, 1990;Mayevsky and Weiss, 1991 ). The increase in blood flow ensures adequate tissue oxygenation and is probably the main factor pre venting spreading depression from producing irre versible neuronal injury in normal animals (Neder gaard .…”
Section: ��--------------------[mentioning
confidence: 99%
“…(1988) demon strated uncoupling of CBF and CMR02 (hyperemia with an increase in CMRglc but not CMR02) even in the normal brain after peripheral nerve stimulation. Supporting the theory of coupling of CBF and me tabolism, measurements of CMRglc and CBF at 3 h after severe (30 min) GBI also showed concurrent hypoperfusion and hypometabolism with normal CBF/CMRglc (Ueki et aI., 1988;Kocher, 1990). Strongly supporting the theory of coupling of CBF and CMR02 during the postischemic hypoperfusion period, Michenfelder et aI.…”
Section: 360mentioning
confidence: 77%